Effect of Concentrated Chaya (Cnidoscolus chayamansa) Vegetable Juice on Quality of Reduced Sugar Roselle Jam - Lichanporn, Intira; Nanthachai, Nanchanok; Tanganurat, Palida; Akkarakultron, Purin (Journal of Applied Research on Science and Technology (JARST), 2021)
The Chaya leaves have been found to be an important source of protein, β-carotene, vitamins, ascorbic acid, calcium, potassium and iron. It is rich in antioxidant and phenolic compound. This study aims to investigate the effect of concentrated Chaya vegetable juice (0 (control; C2), 5, 10, 15 and 20 g on quality of Roselle jam (without pectin) and compared with control (C1; Roselle jam with pectin). Roselle Jam reduced- sugar with concentrated Chaya vegetable juice was evaluated for color, pH, total soluble solid, titratable acidity, stability and sensory properties. Roselle jam reduced-sugar with concentrated Chaya vegetable juice was less dark-red color than C2. The pH of C1 was more than jam from C2, 5, 10, 15 and 20 g of concentrated Chaya vegetable juice. Jam samples showed pH ranging between 2.55-2.59. While, Roselle jam added with concentrated Chaya vegetable juice, C1 and C2 were not significantly different in total soluble solid. The total soluble solid of all Roselle jam ranged between 66 and 68°Brix. The titratable acidity increased with increase in concentrated Chaya vegetable juice. Addition of 10 g concentrated Chaya vegetable juice into Roselle jam showed the highest stability. The sensory score of color, odor, taste, stability of jam and overall acceptance results indicated that Roselle jam processed from 15 and 20 g of concentrated Chaya vegetable juice were generally high. However, the results showed that Roselle jams prepared from concentrated Chaya vegetable juice are still acceptable. Therefore, concentrated Chaya vegetable juice could potentially be used for replacement of the sugar in the formulated jam.